Informal administrative actions in the local territorial planning of Colombia: experiences in territorial governance and enviromental legal deteminants.: Article - Vásquez Santamaría, Jorge Eduardo (Geographicalia, 2023)
How the informal administrative action (AAI) is a legal mechanism of action of the local public administration that, although not regulated, allows the exercise of the public function of urban planning to carry out the purposes and functions of each jurisdiction in cases that are not contemplated by the legal system? is the question that seeks to demonstrate that the AAI gives rise to the execution of local land use planning, an objective that was worked on from the theoretical approach of administrative law as a system (Schmidt-Assmann, 2003), and from a qualitative methodology that applied the hermeneutic method, the case study, and the documentary technique on the Departmental Land Use Plans (POTD), the regulation not mediated by law to develop partial plans, the strategies for the protection of biodiversity, and the prior consultation. Among the results, the cases constitute AAI because they gather most of the elements that characterize them, and from them not only the public function of urban planning takes place, but also new legal determinants of higher environmental hierarchy are being configured.